2021
DOI: 10.1111/jan.15084
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of goal setting on glycaemic control for people with type 2 diabetes and prediabetes: A systematic review and meta‐analysis

Abstract: Aim This review assessed the effectiveness of interventions using a goal‐setting approach on glycaemic control for people diagnosed with prediabetes or type 2 diabetes. Design A systematic review guided by the Joanna Briggs Institute methodology for conducting systematic reviews of primary research studies was conducted. Data Sources Randomized controlled trials and experimental studies with a minimum follow‐up period of 6 months were considered for inclusion. The primary outcome was change in glycaemic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…9 Most recently, a 2022 meta-analysis assessing the effectiveness of interventions using a goal-setting approach on A1c found goal setting more effective than usual care at 6 months (mean difference À.32%, 95% CI À.56, À.08) and 12 months (mean difference À.17%, 95% CI À.33, À.01). 10 Based on our A1c results, our study suggests that SMART goal setting via telehealth with a pharmacist may contribute to additional lowering of A1c compared to other types of goal-setting with different professions. Our study provides new information and a foundation that will guide future research in this area with larger populations.…”
Section: Discussionmentioning
confidence: 61%
“…9 Most recently, a 2022 meta-analysis assessing the effectiveness of interventions using a goal-setting approach on A1c found goal setting more effective than usual care at 6 months (mean difference À.32%, 95% CI À.56, À.08) and 12 months (mean difference À.17%, 95% CI À.33, À.01). 10 Based on our A1c results, our study suggests that SMART goal setting via telehealth with a pharmacist may contribute to additional lowering of A1c compared to other types of goal-setting with different professions. Our study provides new information and a foundation that will guide future research in this area with larger populations.…”
Section: Discussionmentioning
confidence: 61%
“…Given 80% power and a 2-tailed α of .05, we estimated we needed data from 204 dyads to detect a 4-point difference in PAM-13 score changes between groups and 198 dyads to detect a 2% difference in UKPDS score changes. These estimates assumed a baseline mean (SD) PAM-13 score of 70 (13), with correlation of 0.70 in 2 measurements in 1 year, and a baseline mean (SD) UKPDS score of 18% (12%).…”
Section: Discussionmentioning
confidence: 99%
“…9 Interventions that provide general diabetes information to family supporters have not improved patient outcomes. 10,11 Studies on specific aspects of dyadic diabetes management have identified more promising approaches to increasing effective family support, 12 including training family supporters in techniques to facilitate behavior change (eg, goal-setting, 13 action planning, 14,15 and use of autonomy-supportive communication styles [15][16][17][18], enhancing supporter access to information about the patient's diabetes regimen and test results, 19 prompting supporters to routinely discuss diabetes management with the patient, and training supporters in techniques to support patient engagement in health care visits. 20 However, health care teams do not have structured programs or tools to deliver these promising approaches to patient-supporter pairs.…”
Section: Introductionmentioning
confidence: 99%
“…-Models based on community/whānau interventions may serve the needs of high-risk population groups better than individualfocused care -Ensure programmes are designed and delivered in partnership with the populations most adversely affected by T2DM • Models of successful diabetes prevention delivered in PC settings also have a place for some groups 39,52,53 • Clinical guidelines ○ Current 'one-size-fits-all' adult prediabetes guidelines do not reflect what is known about the variable health trajectories of those with prediabetes and create unnecessary burdens on PC service delivery for little gain…”
Section: Policy and Resourcingmentioning
confidence: 99%